FRAGMENTASI HUKUM PERDAGANGAN INTERNASIONAL DI ERA RIVALITAS GEOPOLITIK GLOBAL TANTANGAN MULTILATERALISME DAN PERAN REGIONAL TRADE AGREEMENTS - Dadang Rachmat; Annie Myranika; Ervawati; Dede Agus Sodikin; Djamal Efendi (Berajah Journal, 2026)
The increasingly multipolar nature of the global order has led to the fragmentation of the international trade law system, which was previously built upon the multilateral framework of the World Trade Organisation (WTO). The crisis in the WTO’s Appellate Body since 2019, characterised by the United States’ practice of ‘appealing into the void’, has paralysed the two-tier dispute settlement mechanism that was the hallmark of the multilateral trading system. This phenomenon is exacerbated by the proliferation of Regional Trade Agreements (RTAs), which have reached nearly 600 agreements by 2023, creating overlapping jurisdictions and inconsistent legal interpretations. This study examines, from a normative-legal perspective, how geopolitical rivalry between major powers—the United States, China, and Russia—is accelerating the fragmentation of international trade law through instruments such as economic sanctions, trade wars, and the formation of alternative economic blocs like BRICS. The analysis reveals that legal fragmentation not only threatens the principles of legal certainty and predictability in international trade relations, but also opens the door to the formation of a more adaptive pluralistic legal order in response to the dynamics of national economic security. The study’s conclusions recommend the need for fundamental reform of the Dispute Settlement Understanding (DSU) through a critical mass-based plurilateral decision-making mechanism to address consensus paralysis, as well as the strengthening of ASEAN’s role as a mediator for regulatory harmonisation amidst global economic bloc competition.